2009
DOI: 10.1016/j.bbamem.2009.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of uncoupling protein 4 distribution in various tissues under physiological conditions and during development

Abstract: UCP4 is a member of the mitochondrial uncoupling protein subfamily and one of the three UCPs (UCP2, UCP4, UCP5), associated with the nervous system. Its putative functions include thermogenesis, attenuation of reactive oxidative species (ROS), regulation of mitochondrial calcium concentration and involvement in cell differentiation and apoptosis. Here we investigate UCP4's subcellular, cellular and tissue distribution, using an antibody designed specially for this study, and discuss the findings in terms of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 46 publications
3
61
0
1
Order By: Relevance
“…The prevalence of highly energized mitochondria was observed in the periphery of several cells, including cortical neurons (23). UCP4 may be predominantly located in the neuronal cell body (8), where it would dissipate the excessive proton gradient. This location would also better fit UCP4's function in neuronal metabolism (7,27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of highly energized mitochondria was observed in the periphery of several cells, including cortical neurons (23). UCP4 may be predominantly located in the neuronal cell body (8), where it would dissipate the excessive proton gradient. This location would also better fit UCP4's function in neuronal metabolism (7,27).…”
Section: Resultsmentioning
confidence: 99%
“…Uncoupling protein 1 (UCP1; thermogenin), a member of the UCP subfamily, is known to dissipate the inner membrane proton gradient for heat production. One of the widely discussed functions for UCP4-another member of the same subfamily that is localized in neurons and neurosensory cells (6)(7)(8)(9)-is the regulation of ROS by decreasing the pmf (10,11). Although there is no unambiguous evidence revealing the exact UCP4 function, it was shown that UCP4 transports protons similar to UCP1 (12).…”
mentioning
confidence: 99%
“…The striking absence of these effects from ketone body metabolism in brain is most likely due to the increased expression of uncoupling proteins 4 and 5 in brain and the absence of an increase in uncoupling proteins in heart. Uncoupling proteins 4 and 5 have been shown to be expressed primarily in brain (53,54 The effects of ketone metabolism in brain differs from the acute effects of ketone metabolism in heart most significantly by the lack of an increase in mitochondrial reducing power and the absence of a physiologically significant increase in the ⌬G of ATP hydrolysis. These differences are compatible with the observed increase in UCP 4 and 5, which most likely results from the ability of malonyl-CoA to both increase fatty acid synthesis and decrease the transport of fatty acids into the mitochondria where they can undergo ␤ oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…UCP4 and UCP5 are well expressed in the brain (13,14), and roles in ROS and calcium level regulation (10,15) have been described. In terms of brain cellular localization, immunocytochemistry has revealed that UCP4 is mainly expressed in neurons and less so in astrocytes (16). UCP5 is present in neuronal cell lines (17,18); in the rodent brain, UCP5 expression is observed in the dorsomedial hypothalamic nucleus, hippocampus, paraventricular thalamic nucleus, mediodorsal thalamic nucleus, and ventromedial hypothalamus (13,19).…”
mentioning
confidence: 99%